Total Abdominal Colectomies With Proctectomy Are Associated With Higher 30-Day Readmission Rates in Children With Ulcerative Colitis. Issue 4 (19th May 2020) - Egberg, Matthew D; Phillips, Michael; Galanko, Joseph A; Kappelman, Michael
Abstract: Background: Hospital readmissions are a burden on patients and families and place financial strain on the health care system. Thirty-day readmission rates for adult patients undergoing colectomy are as high as 30%, and inflammatory bowel disease is a risk factor for readmission. We used a multicenter pediatric surgical database to determine the 30-day readmission rate for pediatric patients with ulcerative colitis (UC) undergoing total abdominal colectomy (TAC) and to identify risk factors for 30-day hospital readmission. Methods: We used the National Surgical Quality Improvement Program-Pediatrics database to identify pediatric patients with UC undergoing a TAC between 2012 and 2017. We identified patient and procedural data from the index hospitalization and used logistic regression to identify risk factors for 30-day readmission rates, adjusting for confounding factors. Results: We identified 489 pediatric UC TAC hospitalizations between 2012 and 2017, and 19.4% were readmitted within 30 days of surgical discharge. Patient demographics and preoperative laboratory values were not associated with risk of readmission. The TAC procedures that included a proctectomy were at a 2-fold (odds ratio = 2.4; 95% confidence interval, 1.1-5.2) higher risk of 30-day readmission than TAC alone after adjusted analysis. Conclusions: Nearly 20% of annual pediatric UC hospitalizations involving a colectomy resulted in a 30-day hospital readmission. Notably, TAC procedures that included a proctectomy had significantly higher readmission rates compared to TAC alone. These results can inform risk management strategies aimed at reducing morbidity and hospital readmissions for children with UC.